1999
DOI: 10.1063/1.480274
|View full text |Cite
|
Sign up to set email alerts
|

The influence of buoyant convection on the operation of the upward thermal diffusion cloud nucleation chamber

Abstract: Recently, the stable operation of the upward thermal diffusion cloud chamber with respect to buoyancy-induced convection has become a concern in obtaining reliable nucleation data. During chamber operation, evidence of strong convective currents are clearly visible due to the curved trajectories of entrained droplets. A potential problem exists when these flows are much smaller in magnitude; there is no visible evidence of convection, yet these minute flows may result in systematic errors in the nucleation dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…Recently, the transport in the static diffusion cloud chamber has been reevaluated by a two-dimensional treatment to examine the wall effects and convection on the supersaturation profiles (44)(45)(46)(47). They confirmed that one-dimensional treatment led to essentially the same peak supersaturation under proper conditions (such as a large enough ratio of diameter to height, usually >5, no overheating of the side wall, no convection, etc.).…”
Section: Experimental S Cr and Its Uncertaintymentioning
confidence: 88%
“…Recently, the transport in the static diffusion cloud chamber has been reevaluated by a two-dimensional treatment to examine the wall effects and convection on the supersaturation profiles (44)(45)(46)(47). They confirmed that one-dimensional treatment led to essentially the same peak supersaturation under proper conditions (such as a large enough ratio of diameter to height, usually >5, no overheating of the side wall, no convection, etc.).…”
Section: Experimental S Cr and Its Uncertaintymentioning
confidence: 88%
“…Ferguson and Nuth used a numerical model of the TDCC to show that buoyant convection could result in a reduction of the maximum supersaturation by several percent depending upon a variety of chamber conditions. 14 Schaeffer et al performed a similar analysis, but with higher molecular weight gases. 15 Their results indicated that the TDCC behaves like a classical Rayleigh-Bénard cell, and when conditions exceed a critical value, vigorous convection can occur within the chamber.…”
Section: Introuctionmentioning
confidence: 81%
“…At the upper and lower plates, the temperatures and the mass fraction were kept uniform and constant. Although these two plates are covered with a liquid pool of the condensable species, it is assumed that the velocity components are zero because the liquid layer is so thin that the velocities at the interface can be neglected [10]. Indeed the calculation of evaporating velocity at the lower plate leads to the value of 1.4 · 10 −3 mm/s.…”
Section: Numerical Methods and Boundary Conditionsmentioning
confidence: 99%
“…The nucleation rate is calculated using the classical BeckerDöring-Zeldovitch theory of homogeneous nucleation [15]. The homogeneous rate J can be specified as: (10) where G is the Gibbs free energy of cluster formation, i.e. the elevation of the free energy required for a transition from a monomer to a cluster.…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation